FGFR inhibitors for advanced cholangiocarcinoma - Yang, Tian; Liang, Lei; Wang, Ming-Da; Shen, Feng (The lancet oncology, 2020)
The prognosis of advanced or metastatic cholangiocarcinoma is extremely unsatisfactory, mainly owing to few treatment options and poor responses to conventional chemotherapy regimens.1 Since 2007, advances in next-generation sequencing have substantially improved the ability to understand the complex molecular mechanisms underlying the progression of cholangiocarcinoma.2 The most promising target for cholangiocarcinoma identified in recent years is the fibroblast growth factor (FGF) signalling pathway, which consists of 22 human FGFs and four transmembrane receptor tyrosine kinases (FGF receptors [FGFRs] 1–4).3 Fusions, rearrangements, translocations, and amplifications of FGFR genes are closely related to the initiation and progression of some cancers. Non-selective FGFR inhibitors bind to the conserved ATP-binding domain in receptor tyrosine kinases such as platelet-derived growth factor receptors (PDGFRs) and vascular endothelial growth factor receptors (VEGFRs). Phase 2 trials of the selective FGFR inhibitors erdafitinib (NCT04083976), TAS-120 (NCT02052778), and Debio 1347 (NCT03834220) are undergoing in patients with FGFR alterations, with results from some previous trials suggesting beneficial effects.7,8 In The Lancet Oncology, Ghassan Abou-Alfa and colleagues report the antitumour activity of pemigatinib, a new selective, potent, oral competitive inhibitor of FGFR1, FGFR2, and FGFR3, in 146 patients with advanced or metastatic cholangiocarcinoma who did not respond to at least one previous systemic therapy (the FIGHT-202 trial).9 38 (35·5% [95% CI 26·5–45·4]) of 107 patients with FGFR2 fusions or rearrangements who received pemigatinib achieved an objective response, and the median progression-free survival was 6·9 months (95% CI 6·2–9·6), but the overall survival data were not mature at data cutoff (40 [37%] of 107 patients had died; median overall survival 21·1 months [95% CI 14·8 to not estimable]).